Disease‐Associated Mutations of TREM2 Alter the Processing of N‐Linked Oligosaccharides in the Golgi Apparatus. (24th February 2015) - Park, Ji‐Seon; Ji, In Jung; An, Hyun Joo; Kang, Min‐Ji; Kang, Sang‐Wook; Kim, Dong‐Hou; Yoon, Seung‐Yong
Abstract : The triggering receptor expressed on myeloid cells 2 (TREM2) is an immune‐modulatory receptor involved in phagocytosis and inflammation. Mutations of Q33X, Y38C and T66M cause Nasu‐Hakola disease (NHD) which is characterized by early onset of dementia and bone cysts. A recent, genome‐wide association study also revealed that single nucleotide polymorphism of TREM2, such as R47H, increased the risk of Alzheimer's disease (AD) similar to ApoE4. However, how these mutations affect the trafficking of TREM2, which may affect the normal functions of TREM2, was not known. In this study, we show that TREM2 with NHD mutations are impaired in the glycosylation with complex oligosaccharides in the Golgi apparatus, in the trafficking to plasma membrane and further processing by γ‐secretase. Although R47H mutation in AD affected the glycosylation and normal trafficking of TREM2 less, the detailed pattern of glycosylated TREM2 differs from that of the wild type, thus suggesting that precise regulation of TREM2 glycosylation is impaired when arginine at 47 is mutated to histidine. Our results suggest that the impaired glycosylation and trafficking of TREM2 from endoplasmic reticulum/Golgi to plasma membrane by mutations may inhibit its normal functions in the plasma membrane, which may contribute to the disease. Abstract : Model for trafficking and glycosylation of wild‐type and mutant triggering receptor expressed on myeloid cells (TREM2). Wild‐type TREM2 is normally trafficked and glycosylated from endoplasmic reticulum (ER) to Golgi and plasma membrane. However, Y38C or T66M mutant TREM2 is impaired in this process and accumulated in the ER to induce ER stress. R47H TREM2 is glycosylated differently from the wild type in the Golgi.